2015
DOI: 10.5194/isprsarchives-xl-1-w4-403-2015
|View full text |Cite
|
Sign up to set email alerts
|

Experiments With Uas Imagery for Automatic Modeling of Power Line 3d Geometry

Abstract: Commission I, ICWG I/V-B KEY WORDS: UAS, Dense Matching, Transmission Lines, Modeling ABSTRACT:The ideal mapping technology for transmission line inspection is the airborne LiDAR executed from helicopter platforms. It allows for full 3D geometry extraction in highly automated manner. Large scale aerial images can be also used for this purpose, however, automation is possible only for finding transmission line positions (2D geometry), and the sag needs to be estimated manually. For longer lines, these technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We cannot directly compare the results to that of other studies because the system, the operation condition, and sites are different. But the result is decent that LiDAR systems show elevation accuracy within ±15 cm and previous studies on using aerial images reported the 3D power line extraction accuracy of 0.5 m referring to the ground truth data [15] and the fitting accuracy of 5–9 cm not using the ground truth [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot directly compare the results to that of other studies because the system, the operation condition, and sites are different. But the result is decent that LiDAR systems show elevation accuracy within ±15 cm and previous studies on using aerial images reported the 3D power line extraction accuracy of 0.5 m referring to the ground truth data [15] and the fitting accuracy of 5–9 cm not using the ground truth [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [15] used a fixed wing UAV for the power line inspection proposing a semi-patch matching algorithm based on an epipolar geometry of stereo images. They reported the experimental results of the elevation accuracy of 0.5 m. Jozkow et al [16] carried out the dense image matching for point cloud generation and filtering for the 3D modeling of power lines that they reported a fitting accuracy of 5–9 cm. These approaches follow the conventional image-to-object space approach that is comprised of line detection, image matching, and 3D reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research that used UAVs, it is possible to detect transmission lines under various conditions by using a convolutional neural network for UAV images [3]. In addition, the power line was sufficiently reconstructed by capturing the wire using approximately 10 pixels and reconstructing a three‐dimensional (3D) point cloud so that the position of the wire becomes clear [4]. However, in order to capture the power lines using such methods, it is necessary to capture data from a position close to the power lines, thereby increasing the risk of a UAV touching the power lines.…”
Section: Introductionmentioning
confidence: 99%
“…There has been very little research on the 3D reconstruction of power lines from point clouds generated from multiple UAV images. The analysis of point clouds from UAV imagery for inspecting power lines was discussed for example in [14,15], where it was applied for detecting cable collision with terrain obstacles. Several researchers have proposed to increase the accuracy of extracting power lines from UAV images by improving the radiometry at the stage of preliminary image processing.…”
Section: Introductionmentioning
confidence: 99%